Social Network Analysis of Intensive Care Unit Health Care Professionals Measured by Wearable Sociometric Badges: Longitudinal Observational Study - Kawamoto, Eiji; Ito-Masui, Asami; Esumi, Ryo; Ito, Mami; Mizutani, Noriko; Hayashi, Tomoyo; Imai, Hiroshi; Shimaoka, Motomu (JMIR Publications, 2020)
BackgroundUse of wearable sensor technology for studying human teamwork behavior is expected to generate a better understanding of the interprofessional interactions between health care professionals. ObjectiveWe used wearable sociometric sensor badges to study how intensive care unit (ICU) health care professionals interact and are socially connected. MethodsWe studied the face-to-face interaction data of 76 healthcare professionals in the ICU at Mie University Hospital collected over 4 weeks via wearable sensors. ResultsWe detail the spatiotemporal distributions of staff members' inter- and intraprofessional active face-to-face interactions, thereby generating a comprehensive visualization of who met whom, when, where, and for how long in the ICU. Social network analysis of these active interactions, concomitant with centrality measurements, revealed that nurses constitute the core members of the network, while doctors remain in the periphery. ConclusionsOur social network analysis using the comprehensive ICU interaction data obtained by wearable sensors has revealed the leading roles played by nurses within the professional communication network.